McGregor Ross, H. (trad.): The Gospel of Thomas. Caligrafía de Maclaurin-Jones. V y 112 páginas. “The Ebor Press”. York, 1987. ISBN: 1-85072-019-3. - Fernández, Gonzalo (Gerión. Revista de Historia Antigua, 1988)
Sin resumen